2010
DOI: 10.1002/bit.22890
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic flux analysis of CHO cell metabolism in the late non‐growth phase

Abstract: Chinese hamster ovary (CHO) cell cultures are commonly used for production of recombinant human therapeutic proteins. Often the goal of such a process is to separate the growth phase of the cells, from the non-growth phase where ideally the cells are diverting resources to produce the protein of interest. Characterizing the way that the cells use nutrients in terms of metabolic fluxes as a function of culture conditions can provide a deeper understanding of the cell biology offering guidance for process improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
108
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(118 citation statements)
references
References 35 publications
7
108
2
1
Order By: Relevance
“…The respiratory quotient of cells was constant in metabolic flux analysis, and the value was one (Sengupta et al 2011;Ferreira et al 2005;Duarte et al 2014;Ahn and Antoniewicz 2012). So, the specific rate of CO 2 production was equal to that of O 2 consumption.…”
Section: Methodology Of Mfamentioning
confidence: 99%
See 1 more Smart Citation
“…The respiratory quotient of cells was constant in metabolic flux analysis, and the value was one (Sengupta et al 2011;Ferreira et al 2005;Duarte et al 2014;Ahn and Antoniewicz 2012). So, the specific rate of CO 2 production was equal to that of O 2 consumption.…”
Section: Methodology Of Mfamentioning
confidence: 99%
“…Glutamine and asparagine are the two most consumed amino acids in mammalian cell culture. To achieve high-specific growth rate, cell density, and productivity, the culture should be fed with high levels of glutamine or asparagine (Wlaschin and Hu 2006;Jain and Kumar 2008;Lu et al 2013;Sengupta et al 2011). Specifically, glutamine and asparagine are mutually related to each other not only in transportation but also in metabolism (Wipf et al 2002;Huang et al 2007;Kobayashi et al 2015;Xu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These studies support that the increased NADH generation flux during the SI phase is mainly generated from a higher flux through the TCA cycle. However, Sengupta et al 72 and Templeton et al 73 showed by using isotopic labeling that the flux through both the oxidative PPP as well as through the TCA cycle increased during the non-growth phase. In addition, Ahn and Antoniewicz 60 reported a significant increase in oxidative PPP together with a constant TCA flux from the growth phase to the stationary phase.…”
Section: Metabolic Patterns Of Cell Size Increasementioning
confidence: 99%
“…At the moment, fed-batch is the most common industrial process for CHO cell cultures, due to its ease of operation and flexibility. Three different culture phases can normally be discerned in a fed-batch culture: an exponential growth phase, a stationary phase, and a death phase 60,71,72 . The transitions between these phases are caused by the changes in culture conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation